Cianobactérias heterocitadas e euglenas vermelhas em lavoura de arroz irrigado por inundação em planossolo háplico, Santa Maria, RS - Vasconcellos, Noeli Júlia Schussler de (2010)
Oxyreduction reactions resulting from the soil flood promote lighest availability of nutrients from fertilizer application, soil solution. Although the management of drainage, necessary to improve plant establishment contributes to the loss of fertility in these agroecosystems, events such as leaching, runoff and leakage of water from the blocks with the rains keep this ecosystem enriched and pro- development of phytoplankton. Euglenoids and cyanobacteria are favored by these conditions to grow excessively (blooms) and causing environmental impacts that are applicable to the water bodies receiving drainage waters. Moreover, many of cyanobacteria that develop in these environments also contribute to the maintenance of soil fertility. Within this context, with this work, to characterize populations of heterocytous cyanobacterias that contribute to soil fertility and euglenas red blooms forming in agroecosystem of flooded rice. To achieve these objectives, samples of water and soil in three experimental blocks of rice, and conducted two separate studies: culture, isolation and morfomolecular characterization of heterocytous cyanobacteria and cultivation, morphological characterization, monitoring on site and location of blooms cysts of resistance in the soil, forming euglenas pigmented red blooms. Morphological analysis allowed the characterization of four genera of heterocytous cyanobacteria that contribute to soil fertility: Nostoc, Anabaena, Cilindrospermum and Calotrix. Sequencing of 16S RNA gene was only positive for a strain of the genus Nostoc (Nostoc linckia) which, by phylogenetic analysis showed to be a lineage close to Nostoc sp. TH1S01 e Nostoc piscinale. The results obtained in experiments that were aimed at location of the cysts of resistance suggested that such cysts are found at a depth 0-5 cm of soil, however, focuses more on the surface. For euglenoids there was no evidence of the location of the cysts of resistance even at the surface. Monitoring the appearance of blooms of red euglenas shows that the absence of turbulence in water depths, influenced by wind velocity, and water temperature, influenced by atmospheric temperature and solar radiation are key factors for development. It follows from this work, the dynamics of both populations of cyanobacteria as euglenoids in crop irrigated rice is controlled by many biotic and abiotic making knowledge of their diversity and behavior, in practice very difficult having to therefore, the need to employ different methodologies and continuous monitoring and prolonged. It follows further that the use of in vitro culture, while contributing to the research morfomoleculares, promotes populations changes and further complicates the charactrization of the species.